Diagnosis and Management of High Platelet Reactivity on Treatment with Clopidogrel - Cattaneo, Marco (Seminars in Thrombosis and Hemostasis, 2012)
Clopidogrel is an antithrombotic drug that inhibits the P2Y12 platelet receptor for adenosine diphosphate. Wide interindividual variability of responses to clopidogrel were reported in several studies: about one-third of treated patients exhibit high on-treatment platelet reactivity. Genetic and environmental factors influence the absorption and/or the extent of metabolism of clopidogrel (which is a prodrug) to its active metabolite and this contributes to the observed variability of response. Tailored treatment based on the results of laboratory tests of platelet function was proposed as a solution to this problem. However, we still need to identify the ideal laboratory test and to answer basic questions on its clinical utility and cost-effectiveness, before monitoring clopidogrel therapy can be recommended in clinical practice. When possible, the use of alternative drugs with more uniform and predictable bioavailability and with favorable profiles in terms of risk/benefit and cost/benefit ratios should be preferred.
Keywords: clopidogrel; P2Y12; prasugrel; ticagrelor; acute coronary syndromes